Ekstraksi Teh Hijau dan Aplikasinya sebagai Pengendali Korosi Pada Pompa di Lingkungan Garam NaCl 3,56%: Green Tea Extraction and Its Application as Corrosion Controller in 3.56% NaCl - Retno Indarti (KOVALEN: Jurnal Riset Kimia, 2022)
Green tea leaves contain antioxidant compounds that can be used as organic inhibitors in a corrosion process. Tea leaves were extracted by maceration method using 70% ethanol solution with a solid:solvent ratio of 1:8 (w/v) for 1 x 24 hours in an atmospheric room. The extract was then concentrated with a rotary evaporator and separated with solvent under vacuum conditions at 852 mbar, temperature of 70oC and rotation of 80 rpm. The results of the qualitative test of extra tea leaves using 10% NaOH and 1% FeCl3 changed the color to brownish orange and blue-black. This indicates the content of flavonoids and tannins. Green tea leaf extract is also applied to control the corrosion rate of brass metal. Variations in the concentration of tea leaves were 200, 400, 600 ppm in 3.56% NaCl solution. The pump circulation is carried out for 40 hours, the weight loss method is carried out every 8 hours. The average corrosion rate without inhibitor is 3.95 mmpy, the corrosion rate with 200 ppm inhibitor is 1.24 mmpy, the corrosion rate with 400 ppm inhibitor is 0.46 mmpy, the corrosion rate with 600 ppm inhibitor is 0.23 mmpy. A significant decrease in the corrosion rate occurred at a concentration of 600 ppm with an efficiency of 92.32%.